ERROR OF STUDENTS IN ANSWERING THE QUESTIONS ABOUT CIRCLE MATERIAL FOR THE STUDENTS OF GRADE VIII - Silvia Rachmawati; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Base on the result of the researcher’s interview with one of the mathematics teachers in SMP Negeri 1 Yogyakarta. The teacher claimed that some students still make the error, concept, principle, and operation to answer the circle materials' questions. This research aimed to describe what errors are done by the students and describe the mistakes most often done of the eighth grade of SMP Negeri 1 Yogyakarta in doing the tasks of mathematics, in particular, that were circle materials. This research was descriptive qualitative. The researcher used a test and interview to collect data—the writer interviews with students of class VIII G of SMP Negeri 1 Yogyakarta. The researcher used data reduction, data presentation, and taking the conclusion to analyze the data. The researcher used triangulation to check the validity of data, comparing the result of students' tests and the result of the researcher’s interview. The result of the research showed that students' ability to answer the questions was average. Nevertheless, it should be considered to cause many students who made the error. Those were: 1. Fact error (error in changing the problem into the form of a mathematical model) as much as 5.08%, 2. Concept error (getting the error in understanding mathematics concept) as much as 36,77%, 3. Principle error (getting the error in determining formula) as much as 9,10%, 4. Operation error (getting the error in calculating, mathematics notation, not write denomination, not answer the question) as much as 49,05%. The highest error which was made by students was the error in operation.